ANALISIS KOMPONEN DILALAH DALAM BAHASA ARAB: THE ANALYSIS OF DILALAH COMPONENT IN ARABIC LANGUAGE - Riska Hayati; Nova Ratna Sari Harahap; Erlina (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract: The dalalah component is the smallest component of meaning, some say the expansion or addition of a word that requires an explanation that contains meaning. Semantics is a branch of linguistics that studies the meaning contained in a language, code, or other type of representation. In other words, semantics is the study of meaning. This study of meaning is very important in avoiding mistakes in giving meaning to words and sentences in Arabic texts. Keywords: Components of meaning, knowledge is dilalah Abstrak: Komponen dalalah merupakan komponen terkecil dari makna, ada juga yang mengatakan perluasan atau penambahan dari suatu kata yang membutuhkan penjelasan yang mengandung makna. Semantik adalah cabang linguistik yang mempelajari arti/makna yang terkandung pada suatu bahasa, kode, atau jenis representasi lain. Dengan kata lain, semantik adalah pembelajaran tentang makna. Kajian tentang makna ini sangat penting dalam menghindari kesalahan dalam memberikan makna pada sebuah kata dan kalimat dalam teks berbahasa Arab. Kata kunci: Komponen makna, ilmu dilalah